2018
DOI: 10.1007/s11695-018-3485-4
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic Evaluation of Gastric Specimens After Laparoscopic Sleeve Gastrectomy—an Optimum Screening Test for Incidental Pathologies?

Abstract: During LSG, a thorough visual inspection of the peritoneal cavity along with a macroscopic surgical evaluation of specimen in patients who had preoperative endoscopy with no findings allows to achieve very good specificity and good sensitivity. Therefore, this procedure may be useful as a screening test for incidental pathologies in bariatric patients and may exclude unnecessary histological examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
2
0
3
Order By: Relevance
“…Generally, pre-malignant lesions identified in LSG specimens across 11 studies varied from 4.1 to 33.2% [10,18,[36][37][38][39][40][41][42][43][44]. However, across these 11 abovementioned studies, there was zero actual malignancy reported, despite that these studies were undertaken in a wide variety of geographical areas worldwide with different risk of gastric cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, pre-malignant lesions identified in LSG specimens across 11 studies varied from 4.1 to 33.2% [10,18,[36][37][38][39][40][41][42][43][44]. However, across these 11 abovementioned studies, there was zero actual malignancy reported, despite that these studies were undertaken in a wide variety of geographical areas worldwide with different risk of gastric cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, even with our 7.5% pre-malignant lesions identified in LSG specimens, and with the huge number of LSG procedures undertaken worldwide, such current lack of the evidence base renders us unable to extrapolate in any way the potential number of patients with pre-malignant lesions that would actually turn malignant or whether such numbers would be high and alarming or otherwise. Hence, there exists much debate regarding the role of routine histopathological examination of LSG specimens [10,18,[36][37][38][39][40][41][42][43][44], and some authors have suggested that histopathological examination of LSG specimens is to be done when intraoperative macroscopic pathology is observed [10,18,43]. Future research would benefit from addressing these points.…”
Section: Discussionmentioning
confidence: 99%
“…Bir çalışmada, makroskopik değerlendirme mikroskobik değerlendirme ile karşılaştırılmış ve olguların %75'inde makroskopik değerlendirmenin patolojileri ortaya çıkardığını ve %99,1 gibi yüksek bir negatif tahmin değeri sunduğunu belirtmişlerdir (23) .…”
Section: Discussionunclassified
“…Genel olarak, LSG'de tanımlanan pre-malign lezyonlar 11 çalışmada %4,1 ila 33,2 arasında değişmiştir (8,18,23) . Bununla birlikte, yukarıda söz edilen bu 11 çalışmada, sıfır gerçek malignite olduğu bildirilmiştir.…”
Section: Discussionunclassified
See 1 more Smart Citation